Walking up the Down Escalator : Public Investment and Fiscal Stability - Easterly, William; Irwin, Timothy; Servén, Luis (World Bank, 2012)
When growth-promoting spending is cut so much that the present value of future government revenues falls by more than the immediate improvement in the cash deficit, fiscal adjustment becomes like walking up the down escalator. Although short-term cash flows matter, too tight a focus on them encourages governments to invest too little. Cash-flow targets also encourage governments to shift investment spending off budget by seeking private investment in public projects, irrespective of its real fiscal or economic benefits. To deal with this problem, some observers have suggested excluding certain investments (such as those undertaken by public enterprises deemed commercial or financed by multilaterals) from cash-flow targets. These stopgap remedies may help protect some investments, but they do not provide a satisfactory solution to the underlying problem. Governments can more effectively reduce the biases created by the focus on short-term cash flows by developing indicators of the long-term fiscal effects of their decisions, including accounting and economic measures of net worth, and, where appropriate, including such measures in fiscal targets or even fiscal rules.